2018
DOI: 10.1002/jcb.27439
|View full text |Cite
|
Sign up to set email alerts
|

Computational optimization of in vitro parameters for di‐(2‐ethylhexyl) phthalate production from Anabaena circinalis

Abstract: Di-(2-ethylhexyl) phthalate (DEHP) is a ubiquitous environmental toxicant, and finds extensive commercial application as a plasticizer to reduce the rigidity of polyvinyl chloride. Besides numerous negative impacts on environment and public health, the compound exhibits acute bioactivity against microbes and has therapeutic value too. Considering this biochemical significance, searching of its new biogenic sources has become an active area of research. Here, DEHP is identified from the biomass of a toxic strai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 33 publications
1
2
0
Order By: Relevance
“…The ESI-MS/MS analysis ( Figure 5 ) also supported the findings. The results of spectral data were correlated with previous findings in the literature [ 25 , 31 , 34 , 35 ]. This metabolite is also known as Di-(2-ethylhexyl) phthalate (DEHP) and Bis (2 ethyl hexyl) Benzene-1,2-dicarboxylate.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…The ESI-MS/MS analysis ( Figure 5 ) also supported the findings. The results of spectral data were correlated with previous findings in the literature [ 25 , 31 , 34 , 35 ]. This metabolite is also known as Di-(2-ethylhexyl) phthalate (DEHP) and Bis (2 ethyl hexyl) Benzene-1,2-dicarboxylate.…”
Section: Discussionsupporting
confidence: 85%
“…Furthermore, in the current study the BEHP also showed DNA damage ( Table 5 and Figure 6 ) in C. quinquefasciatus , suggesting that BEHP could bind with the DNA of organisms. The binding could affect the replication process, thereby causing the death of susceptible organisms [ 35 , 43 ] through the mechanisms not studied yet. The observed mortality of C. quinquefasciatus larvae can be caused by the modulate AChE enzymatic activity and can also be attributed due to DNA damage [ 44 ].…”
Section: Discussionmentioning
confidence: 99%
“…As we will see in the next sections on the efficiency of bioaccumulation and the biodegradation of phthalates, environmental parameters also play a fundamental role in the biosynthesis of phthalates. This was observed in cyanobacteria Anabaena circinalis, where factors such as light, temperature, and nutrients were found to affect the production of DEHP [52].…”
Section: Biosynthesismentioning
confidence: 87%